OUTPUT-PRICE DYNAMICS IN THE ASEAN-5 COUNTRIES: Evidence from The Pre- and Post-1997 Financial Turmoil - Hj. Kassim, Salina; Abd. Majid, M. Shabri (Gadjah Mada International Journal of Business, 2008)
We analyze the cyclical behavior between outputs and prices in major ASEAN economies, namely Malaysia, Indonesia, Thailand, Singapore and the Philippines over two sample periods: the pre-crisis period (1990 to 1996) and the post-crisis period (2000 to 2006). Specifically, the study aims to shed the light on two issues: (i) the possibility that there is a change in the patterns of the correlations between real activities and prices in a particular country in the pre-crisis period compared to the post-crisis period; and (ii) the synchronization of real activity and price relationships or the business cycles across the major ASEAN countries. In order to analyze the output-price relationship across the countries and time periods, we adopt several tests including the Pearson correlation analysis, Auto-Regressive Distributed Lag (ARDL) model and Vector Error-Correction Model (VECM). The study documents that the output-price relationship has changed in several countries following the crisis in 1997/1998. While there is a clear business cycles synchronization between the ASEAN-5 countries in the short-run, results have been mixed in the long run. Results of this study contribute towards further enriching the policy recommendations to help ensuring the viability and effectiveness of the economic cooperation between the ASEAN nations.